COMPARISON OF LIPID PROFILE LEVELS IN PATIENTS WITH ISCHEMIC STROKE AND HEMORRHAGIC STROKE AT RADEN MATTAHER HOSPITAL JAMBI - Alfi Khaira; Mirna Marhami Iskandar; Nyimas Natasha Ayu Shafira (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Stroke attacks the brain, causing neurological disorders and even death. In 2023, there were 337 stroke cases at RSUD Raden Mattaher Jambi. Objective: This study aims to analyze differences in lipid profile levels between patients with ischemic and hemorrhagic strokes at Raden Mattaher Hospital in 2023. Methods: This study used a cross-sectional comparative analytical design with a quantitative approach, and the sample consisted of 101 ischemic and 101 hemorrhagic stroke patients, each selected through purposive sampling. Results: Findings showed that the majority of ischemic and hemorrhagic stroke patients were aged 56-65 years. Ischemic stroke patients were predominantly female, while men were predominantly affected by hemorrhagic stroke. Most stroke patients had normal pulse rate and body temperature, with blood pressure most frequently in stage 2 hypertension. Respiratory rates were normal in ischemic stroke patients but showed tachypnea in hemorrhagic stroke. Triglyceride and LDL levels were higher on average in ischemic stroke patients, while total cholesterol and HDL levels were higher in hemorrhagic stroke patients. Conclusion: Significant differences were observed in lipid profile components, specifically triglycerides, HDL, and LDL, between patients with ischemic and hemorrhagic strokes. However, there was no significant difference in total cholesterol levels.